Didactic Foundations of Professional Socialization of Future Elementary School Teachers (Open Academia: Journal of Scholarly Research, 2023)
This article delves into the didactic foundations that underpin the professional socialization of future elementary school teachers. The process of preparing educators for the dynamic and demanding field of elementary education requires a solid pedagogical framework. By examining the didactic principles, strategies, and approaches essential for shaping the next generation of elementary school teachers, this study aims to enhance the quality and effectiveness of teacher education programs. Understanding these foundations is crucial for educators and policymakers striving to foster a skilled and compassionate cadre of educators.